Strategies for Developing The Creative Economy of Small and Medium Enterprises Producing Dodol Straberry Bandung Digital Marketing-Based Digital Marketing - Lulu Febriany (PT Bukuloka Literasi Bangsa, 2025)
This study aims to analyze digital marketing-based creative economy development strategies for strawberry dodol MSMEs in Rancabali Patengan Village, Bandung. The method used is Qualitative Descriptive with a Participatory Community Service (PkM) approach, through observation, interviews, and documentation. The analysis was conducted using the Analytical Hierarchy Process (AHP) to determine the priority of digitization strategies. The results show that strengthening human resource capacity is the top priority with a weight of 38.2%, followed by product and packaging innovation (27.5%), digital infrastructure (21.3%), and cross-sector collaboration (13.0%). The implementation of digital marketing has been proven to increase sales by up to 32% and expand the online market reach of MSMEs. This activity had a significant impact on improving digital literacy, strengthening local identity, and economic independence of the community. Key recommendations include continuous digital training, the formation of village branding teams, and strategic partnerships with the private sector. Keywords: Creative Economy, Digital Marketing, MSMEs, Strawberry Dodol, AHP, Rancabali.